KEMALİYE (ERZİNCAN) İLÇESİ SU KENELERİNİN (ACARİ:HYDRACHNİDİA) SİSTEMATİK YÖNDEN İNCELENMESİ - DİLKARAOĞLU, SİBEL (Fırat Üniveristesi, 2012)
Bu çalışmada, Kemaliye'den toplanan su keneleri değerlendirilmiş ve toplam 17 familyaya ait 76 tür tespit edilmiştir. Bu türlerden; Lebertia (Brentalebertia) anatolica sp. nov. bilim dünyası için; Sperchon (Hispidospercon) algeriensis (Lundblad, 1942), Atractides (s.str.) glandulosus (Walter, 1918) ve Atractides (s.str.) nahavandii Schwoerbel & Sepasgozarian, 1976 Türkiye faunası için yeni kayıttır. Ayrıca, Lebertia (s.str.) rivulorum K. Viets, 1933'un dişisi ilk defa yakalanmıştır. Tespit edilen türlerin tümü Kemaliye için; Arrenurus (Micruracarus) forpicatus Neuman, 1880 ve Arrenurus (s.str.) robustus Koenike, 1894 hariç, Erzincan ili için yeni kayıttır.Teşhis edilen tüm türlerin morfolojik özellikleri, çeşitli organlarının ölçümleri, kısa tanımları, yaşama ortamları ile Türkiye'deki ve dünyadaki yayılışları verilmiştir. Ayrıca, Türkiye faunası için yeni kayıt ve bilim dünyası için yeni olan türlerin şekilleri verilmiştir.Anahtar Kelimeler: Kemaliye, Su kenesi, Acari, Hydrachnidia, Sistematik, Türkiye.

In this study, it was evaluated water mite species collected from Kemaliye. Totally, it was identified 76 species belonging to 17 families. Of these, Lebertia (Brentalebertia) anatolica sp. nov. is new for science; Sperchon (Hispidospercon) algeriensis (Lundblad, 1942), Atractides (s.str.) glandulosus (Walter, 1918) and Atractides (s.str.) nahavandii Schwoerbel & Sepasgozarian, 1976 are newly recorded for the Turkish fauna. Furthermore, the female of Lebertia (s.str.) rivulorum K. Viets, 1933 was collected for the first time in Turkey. All identified species are new records for Kemaliye; except Arrenurus (Micruracarus) forpicatus Neuman, 1880 and Arrenurus (s.str.) robustus Koenike, 1894, others were newly recorded for Erzincan Province.The morphological characters, the measurements of various organs, the short descriptions, habitats and their distributions on Turkey and on the world of all identified species were given. Furthermore, it was also given the drawings of various organs of species that are newly recorded for the Turkish fauna and new to science.Keywords: Kemaliye, Water mite, Acari, Hydrachnidia, Systematic,Turkey.
A systematic study on water mites (Acari:Hydrachnidia) of Kemaliye district (Erzincan province)
Keywords: Zooloji